Pengaruh Latihan Pukulan Menggunakan Imagery Terhadap Hasil Smash Permainan Bola Voli Tim Putra Penjaskesrek Universitas Islam Riau Pekanbaru - Candra, Alfi; Henjilito, Raffly (Journal Sport Area, 2018)
This study aimed to determine the effect of smash training by using Imagery toward smash result of Men Volleyball team ofHealth, Physical education and recreation Department of Teacher Training and Education Faculty of Universitas Islam Riau. This research designwas quasi experimental with one group pretest-posttest design. The population of this research was all players of Men Volleyball team of Health, Physical education and recreation Department of Teacher Training and Education Faculty of Universitas Islam Riau. The sample of this research was allpopulation or also called as total sampling which consisted of 14 students. The test used wasvolleyball smash l. The data was analyzed statistically by dependentt-test. The result shown that there was no significant effectof using Imagery training of students’ smash results. Then, experimental treatments with Imagery exercise were done for 12 meetings, (post-test) was a passing and stopping skill test which had result as 1398 and the mean score was99.86, and t-observe was 0.17 which means bigger than significant value of t-tableas 2.16. As conclusion, Ho isaccepted, and Hais rejected.